1996
DOI: 10.1159/000177970
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Two Dairy Fats on Lipid Synthesis in the Pig: Comparative Study of Liver, Muscle and the Two Backfat Layers

Abstract: The development of pig adipose tissues is influenced by several factors such as localisation and dietary fat. The neck and backfat subcutaneous adipose tissues consist of two layers with different chemical compositions, and it is not yet known whether such variations are due to differences in lipogenic enzyme activities or to other factors. The aim of the present study was to compare the lipogenic activities of tissues from different sites (Longissimus dorsi muscle, liver, subcutaneous backfat) and between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
2
25
1
Order By: Relevance
“…Fatty acid compositions of three different tissues and, in particular, the MUFA and PUFA content are highly dependent on the fat composition of the diet by de novo synthesis or by elongation from fatty acids provided by the dietary fats. [16][17][18] This was profoundly significant with linoleic acid and oleic acid in our data. Therefore, the steady state composition of fatty acids in tissues, i.e., the proportions of SFA, MUFA, and PUFA could be maintained by different esterifying enzymes actions, i.e., on site remodeling of fatty acid esters in accordance with the PI is calculated as an index of substrate availability for maximal rates of oxidation with two or more double bonds and is based on the formula of in vitro experiment.…”
Section: Discussionmentioning
confidence: 48%
“…Fatty acid compositions of three different tissues and, in particular, the MUFA and PUFA content are highly dependent on the fat composition of the diet by de novo synthesis or by elongation from fatty acids provided by the dietary fats. [16][17][18] This was profoundly significant with linoleic acid and oleic acid in our data. Therefore, the steady state composition of fatty acids in tissues, i.e., the proportions of SFA, MUFA, and PUFA could be maintained by different esterifying enzymes actions, i.e., on site remodeling of fatty acid esters in accordance with the PI is calculated as an index of substrate availability for maximal rates of oxidation with two or more double bonds and is based on the formula of in vitro experiment.…”
Section: Discussionmentioning
confidence: 48%
“…The outer layer is richer in unsaturated fatty acids (Malmfors et al, 1978) and in collagen tissues with greater organization of the connective structure surrounding the adipocytes (Lo Fiego et al, 1987) that gives it a greater consistency compared with the inner layer. The lipogenic activities are greater in the inner layer than in the outer layer (Camara et al, 1996;Warnants et al, 1999).…”
Section: Introductionmentioning
confidence: 90%
“…The subcutaneous fat of pigs is constituted by two (Camara et al, 1996) or more layers (Apple et al, 2009) with different chemical compositions and different metabolic activity. In fact it should not be considered as a single entity, but rather as two separate tissues (Camara et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that dietary fatty acid composition can influence different integrating processes of lipid metabolism, such as adipose tissue lipolysis (Awad & Chattopahyay 1986a,b;Raclot et al 1997;Portillo et al 1999b), lipogenesis (Perdereau et al 1992;Camara et al 1996;Portillo et al 2001), lipoprotein lipase activity (Murphy et al 1993;Raclot et al 1997), thermogenic capacity (Takeuchi et al 1995;Kawada et al 1998;Takahashi & Ide, 2000;Rodríguez et al 2002) and fatty acid oxidation (Leyton et al 1987). The potential influence of dietary fatty acids on expression of ob gene and secretion of leptin remains to be elucidated.…”
mentioning
confidence: 99%